Psychoactive substance the examination of implements and school factors among young persons living on country - Barabásné Kárpáti, Dóra (Acta Agraria Debreceniensis, 2009)
The study investigates the drug addiction, school problems and the underlying emotional disorders of provincial young people. I assumed that school problems are connected with theyouth’s legal and illegal drug consumption.In my research, I used the Euroadad questionnaire taken at the Drug Ambulance of Nyíregyháza. The sample covered 144 interviewees, 76.9% of whom were „diverted” from jurisdiction. The other respondents volunteered for the therapy.The linear regression analysis was applied to examine the interrelations between the elements under study.All of the 144 respondents have tried or regularly apply some consciousness-modifying substance. Most of them are young adults. The preferred drugs were marijuana and ecstasy. Allconsume alcohol as well. A significant connection can be proved between the majority of the psychological and school behavioural problems under survey and the drug abuse. The more problematic group covers those taking extasy.